1980
DOI: 10.1037/0735-7028.11.3.428
|View full text |Cite
|
Sign up to set email alerts
|

Career development in work organizations: Research and practice.

Abstract: Career development has become "big business" over the last few years, and this article is a review of the state-of-the-art of career development. Both research and practice are reported and covered under four categories: (a) recent research developments, (b) recent career program development, (c) a critical evaluation of these developments, and (d) possible future trends. All stages of development are surveyed, not only the early and later periods. Schein's concept of career anchor is duly considered, with att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Research has shown that the best development occurs on the job (Hall and Associates, 1986). In fact, Seibert, Hall, and Kram (1995) maintained that development strategies that are built on naturally occurring work experiences are more flexible and responsive and thus better suited to current conditions.…”
Section: Hypothesis 2 a Manager's Satisfaction With Employee Developmentioning
confidence: 95%
“…Research has shown that the best development occurs on the job (Hall and Associates, 1986). In fact, Seibert, Hall, and Kram (1995) maintained that development strategies that are built on naturally occurring work experiences are more flexible and responsive and thus better suited to current conditions.…”
Section: Hypothesis 2 a Manager's Satisfaction With Employee Developmentioning
confidence: 95%
“…In this status, the work environment and the cultural context are highly influential in enhancing or blocking successful outcomes. Therefore, organizational career theory (Hall & Associates, 1986) is also particularly applicable to this status. Finally, because Maintaining involves balancing work and other life roles, Super's life-career rainbow is applicable to this status.…”
Section: Maintaining Statusmentioning
confidence: 99%
“…T o address the needs of both the organization and the individual, career development programs consist of two separate but interrelated functions: (1) career planning and (2) career management (Hall, 1987).…”
Section: Career Planning a N D Career Managementmentioning
confidence: 99%
“…Since the recessions of 1979 and 1982, top managements have realized that the organizations alone could not possibly provide all the career rewards an employee may seek (Hall, 1987). This realization of employee needs has made the identification of individuals for top management positions very difficult.…”
mentioning
confidence: 96%